Electrochemical sensing using magnetic molecularly imprinted polymer particles previously captured by a magneto-sensor - Ruiz-Córdova, Gerson A. [UNESP]; Khan, Sabir [UNESP]; Gonçalves, Luís Moreira; Pividori, Maria Isabel; Picasso, Gino; Sotomayor, Maria Del Pilar T. [UNESP] (Elsevier, 2018)
The determination of 1-chloro-2,4-dinitrobenzene (CDNB) was used as a proof-of-concept to a simple analytical practical configuration applying magnetic molecularly imprinted particles (mag-MIPs). Mag-MIPs were captured from an emulsion by a home-made magneto-sensor (where a small magnet was entrapped by a graphite-epoxy composite) and then, this sensor, was transferred to the solution containing the analyte, where, after binding to the mag-MIPs, the analyte was directly analysed using differential pulse voltammetry (DPV) since the magneto-sensor acted as the working electrode. After optimization, a detection limit of 6.0 μmol L−1 with a RSD of 2.7% was achieved along with suitable recoveries and selectivity. This methodology offers a different approach for electroanalytical methodologies using mag-MIPs.
Keywords: 2,4-Dinitrochlorobenzene (CDNB); Electroanalysis; Magnetic beads; Modified working electrode; Nanoparticles; Stripping voltammetry